З історії лексики української ділової мови (довіреність, доручення) - Боярчук, О. (Лексикографічний бюлетень, 2011)
Ukrainian official-business language lexis and phraseology is currently in the phase of formation and unification. The article is dedicated to the issue of functioning of two Ukrainian official-business language terms – довіреність and доручення. The usage of these terms is still inexact. Thus this issue needs to be thoroughly studied. To study the history of two aforementioned terms in the Ukrainian official-business language, we appealed not only to contemporary interlingual official-business, law, and banking language dictionaries, but also to the dictionaries published in Ukraine during the twentieth century. To achieve the legal certainty in the usage of these terms in the meaning of “a document by which somebody is granted power of attorney”, we should choose only one of them. As far as the term доручення has a little bit different connotation and it is an equivalent to the Russian lexeme “поручение”, the most optimal alternative may be to leave the term довіреність.